Pengaruh Model Pembelajaran Kooperatif Tipe Cooperative Integrated Reading and Compositi (CIRC) dan Minat Baca Terhadap Keterampilan Menulis Karangan Deskripsi Siswa Kelas X SMA Negeri 1 Bangkinang - Anita, Fenny (GERAM: Gerakan Aktif Menulis, 2020)
This research was conducted to explain the effect of the learning model CIRC and reading interest on the results of the descriptive essay writing skills of class X SMA Negeri 1 Bangkinang. This type of research is a quantitative study using a quasi-experimental method and a 2x2 factorial experimental design. The population of this study was students of class X SMA Negeri 1 Bangkinang. Sampling was done by purposive sampling with a sample size of 60 students. Data collection was carried out using two instruments, namely questionnaires and performance tests. Based on the research results, it can be concluded that four things are as follows. First, the skills of writing essays of descriptions of students taught using the learning model CIRC are better than those taught by conventional learning models of class X students of SMA Negeri 1 Bangkinang. Second, the writing skills of students who have high reading interest who are taught using the learning model CIRC are higher than students who have high reading interest who are taught using the conventional learning model of class X students of SMA Negeri 1 Bangkinang. Third, the writing skills of students who have low reading interest who are taught using the learning model CIRC are higher than students who have low reading interest who are taught using the conventional learning model of class X students of SMA Negeri 1 Bangkinang. Fourth, there is no interaction between reading interest and learning models in influencing the writing skills of descriptive essays of class X SMA Negeri 1 Bangkinang.